Association between epidural-related maternal fever and short-and long-term prognosis of parturients: A prospective observational study - Li, Bing; Liao, Yicong; Wang, Qingning; He, Shiyuan; Yang, Lulu; Jia, Junxiang; Zhao, Baisong (Frontiers in Surgery, 2023)
We aimed to explore the association between epidural-related maternal fever (ERMF) and prognosis of parturients. 159 parturients who underwent vaginal delivery under labor epidural analgesia (LEA) received noninvasive continuous core body temperature monitoring. 122 of them completed the 42-day postpartum follow-up. Parturients with body temperature ≥38°C during labor were categorized as the Fever group, while the others were categorized as the No-Fever group. Compared to No-Fever group, Fever group had a greater proportion of primiparas, greater gestational age of parturients, and longer third stage of labor. The cesarean section and forceps delivery rates, and the amount of intrapartum hemorrhage in Fever group were significantly higher. There were no significant between-group differences with respect to puerperal infection, and amniotic fluid turbidity degree, neither significant between-group difference at 42-days postpartum. We found that ERMF was associated with some short-term outcomes. However, it showed no relation with long-term prognosis of the parturients at 42-days postpartum.